2018
DOI: 10.17079/jkgn.2018.20.s1.s127
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of Geriatric Nursing Application Based on Robot Technology

Abstract: The purpose of this study was to investigate the possibility of using intelligent robot based nursing practice as discussed in previous research and also, to propose directions for robot care for elders. Methods: For this study 28 previous researches using robots in health care field were reviewed and related research trends introduced. Results: Robot applications in the healthcare field were mainly for rehabilitation, surgery, interaction, and nursing assistance through robotics. Especially types of robot inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Previous studies have reported that the care robot industry has a high growth potential. In order to realize their potential as a new industry, care robots should be marketed with high usability in order to reflect the close relationship between the product and the user, as well as the link between technology innovation and the environment and social systems, as realized through organizational innovation [ 3 , 25 ]. Organizational innovation is essential for the potential development of new industries [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the care robot industry has a high growth potential. In order to realize their potential as a new industry, care robots should be marketed with high usability in order to reflect the close relationship between the product and the user, as well as the link between technology innovation and the environment and social systems, as realized through organizational innovation [ 3 , 25 ]. Organizational innovation is essential for the potential development of new industries [ 26 ].…”
Section: Discussionmentioning
confidence: 99%